Microbial production of vitamin B(12): a review and future perspectives - Fang, Huan (Microb Cell Fact, 2017)
Vitamin B(12) is an essential vitamin that is widely used in medical and food industries. Vitamin B(12) biosynthesis is confined to few bacteria and archaea, and as such its production relies on microbial fermentation. Rational strain engineering is dependent on efficient genetic tools and a detailed knowledge of metabolic pathways, regulation of which can be applied to improve product yield. Recent advances in synthetic biology and metabolic engineering have been used to efficiently construct many microbial chemical factories. Many published reviews have probed the vitamin B(12) biosynthetic pathway. To maximize the potential of microbes for vitamin B(12) production, new strategies and tools are required. In this review, we provide a comprehensive understanding of advances in the microbial production of vitamin B(12), with a particular focus on establishing a heterologous host for the vitamin B(12) production, as well as on strategies and tools that have been applied to increase microbial cobalamin production. Several worthy strategies employed for other products are also included.